FOOD SECURITY: A PANACEA FOR ECONOMIC DEVELOPMENT IN NIGERIA - Goyilla, Abigail Elisha; Abubakar, Omaku A.; Abdullahi, Abubakar Okuwa (African Journal of Social and Behavioural Sciences, 2024)
This study examines food security as a bedrock for achieving national development in Nigeria. Nigeria is the most populated country in Africa with more than 200 million people but food insecurity has remained a constraining factor in the realization of its national development. Despite its huge natural resource endowment, Nigeria still faces hunger, malnutrition and poverty. In spite of the various agricultural policies and projects embarked by the government to boost agricultural productivity, achieving food security has remained a major challenge. One of the indices used in measuring a nation’s development is the level of food and nutrition available to its citizens. The qualitative approached method was applied and, materials were analysed through the content approach. Data for the study was sourced through secondary means while relevant information was gathered from textbooks, government publications and other articles. The study reveals that it will be difficult for Nigeria to achieve its national development goals if food insecurity is not addressed. Amongst other recommendations, this study recommends the strengthening of anti-corruption agencies and the introduction of modern digital technology to revamp the agricultural sector and make farming attractive to young people.